2005
DOI: 10.1097/01.brs.0000171907.60775.85
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dilute Betadine Solution Irrigation in the Prevention of Postoperative Infection of Spinal Surgery

Abstract: Our report is the first prospective, single-blinded, randomized study to evaluate the clinical effectiveness of dilute betadine solution irrigation for prevention of wound infection following spinal surgery. We recommended this simple and inexpensive measure following spinal surgery, particularly in patients with accidental wound contamination, risk factors for wound infection, or undergoing surgery in the absence of routine ultraviolet light, laminar flow, and isolation suits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 35 publications
2
149
0
2
Order By: Relevance
“…They use, in addition, jet lavage irrigation with detergent solution [31] before closure, with early results suggesting a much smaller infection rate. Another preventive measure was described by Cheng et al [32] in a prospective, randomised study. They found that irrigation of the spinal wound with dilute Betadine solution completely prevented infection in a group of 208 patients compared with a 2.9% rate in 206 patients who did not have Betadine irrigation.…”
Section: Preventionmentioning
confidence: 99%
“…They use, in addition, jet lavage irrigation with detergent solution [31] before closure, with early results suggesting a much smaller infection rate. Another preventive measure was described by Cheng et al [32] in a prospective, randomised study. They found that irrigation of the spinal wound with dilute Betadine solution completely prevented infection in a group of 208 patients compared with a 2.9% rate in 206 patients who did not have Betadine irrigation.…”
Section: Preventionmentioning
confidence: 99%
“…Very few literature are available for use of intraoperative irrigation of antiseptics or antimicrobial solution as a prophylaxis of post operative infection in spine surgery. 25,26 One patient had dural tear and required laminectomy for repair. Incidental dural tear has been reported in 3% case by Pearson AM et al 27 Resurgeries for recurrent herniation has been reported 4 to 48% in various series.…”
mentioning
confidence: 99%
“…A 10 % povidone-iodine solution was diluted to achieve a concentration of 3.5 % betadine, possessing maximal bactericidal activity and minimal cytotoxicity. No wound infection occurred in patients who received betadine irrigation during the follow-up period [26].…”
Section: Discussionmentioning
confidence: 99%